Hubungan Pengetahuan Ibu Hamil Dengan Kepatuhan Pemeriksaan Triple Eliminasi Di Puskesmas L. Sidoharjo Kabupaten Musi Rawas Sumatera Selatan - Rahmawati, Ika; Yulianti, Syami; Annisa, Kintan (Utami Publisher, 2025)
Pregnancy with HIV (Human Immunodeficiency Virus), Syphilis and Hepatitis B is caused by viruses that are similar in their mode of transmission. HIV in pregnant women is increasing and is found in the age of 20-29 years. The prevalence of pregnant women with HIV is 0.39%, pregnant women with syphilis 1.7% and pregnant women with Hepatitis B 2.5%. The purpose of this study was to determine the relationship between knowledge of pregnant women and compliance with triple elimination checks at Puskesmas L.Sidoharjo, Musi Rawas Regency, South Sumatra. This type of research is correlational analytic research with cross sectional design. The sampling technique used is proportional random sampling. The sample used in this study were all pregnant women who did antenatal checks at Puskesmas L.Sidoharjo, Musi Rawas Regency, South Sumatra which met the inclusion criteria of 70 respondents. The results showed that 39 (55.7%) respondents knew about triple elimination, only 30 (76.9%) respondents were compliant with triple elimination checks. The Chi Square test results show a p value = 0.027. Based on these results, it is concluded that there is a relationship between the knowledge of pregnant women and compliance with triple elimination checks. It is recommended that pregnant women carry out the recommendations that have been given in conducting triple elimination checks so as to reduce maternal and infant morbidity and mortality.